Effect of injection depth of digestate liquid fraction on soil carbon dioxide emission and maize biomass production - Maucieri, Carmelo; Barbera, Antonio C.; Borin, Maurizio (Italian Journal of Agronomy, 2016)
The aim of this study was to evaluate, in open field conditions, the effect of injection depth of digestate liquid fraction (10 cm, 25 cm and 35 cm) in clay loam soil, on CO2 emission. An un-amended soil was considered as control. The study was performed in 2014 on a farm located in Terrasa Padovana, Veneto region (Italy) distributing digestate before maize sowing. Digestate injection determined a high soil CO2 emission in the first hour after application, followed by a progressive reduction in as early as 24 h, reaching significantly lower values, similar to those measured in the un-amended control, after 48 h. Gas emissions measured 1 h after digestate application decreased as injection depth increased with significantly higher emission values in the 10 cm treatment (median value 23.7 g CO2 m–2 h–1) than in the 35 cm one (median value 2.5 g CO2 m–2 h–1). In the 3 days between digestate distribution and maize sowing, soil CO2 emission was significantly higher in the amended treatments than un-amended one, with median values of 1.53 g CO2 m–2 h–1 and 0.46 g CO2 m–2 h–1 respectively. During maize growing season, no significant soil CO2 emission difference was monitored among treatments, with a median value of 0.33 g CO2 m–2 h–1. Digestate application significantly improved maize aboveground dry biomass with an average yield of 22.0 Mg ha–1 and 16.2 Mg ha–1 in amended and un-amended plots, respectively, due to the different amount of nutrients supplied.